2010
DOI: 10.1557/proc-1246-b07-12
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Oxide Assisted n-type Dopant Diffusion in 4H-Silicon Carbide

Abstract: Phosphorus is an important n-type dopant for both silicon and silicon carbide. Although solid-state diffusion of phosphorus in silicon has been well documented and experimentally proven, not much is known about phosphorus solid-state diffusion in silicon carbide, especially at lower temperatures. A convenient source of phosphorus for solid-state diffusion in silicon carbide is phosphorus oxide. The possibility of using phosphorus oxide as a dopant source for silicon carbide is investigated by considering the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The solid-state diffusion method does not require toxic phosphine gas or pyrophoric liquid source and therefore does not pose any safety or environmental issue. In our study of low temperature impurity doping of SiC, we have found that phosphorus impurity doping of SiC can be carried out below 1400°C by solid state diffusion when assisted by a process to intentionally create vacancies [1,2,3]. Such process includes oxidation or silicidation [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-state diffusion method does not require toxic phosphine gas or pyrophoric liquid source and therefore does not pose any safety or environmental issue. In our study of low temperature impurity doping of SiC, we have found that phosphorus impurity doping of SiC can be carried out below 1400°C by solid state diffusion when assisted by a process to intentionally create vacancies [1,2,3]. Such process includes oxidation or silicidation [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In our study of low temperature impurity doping of SiC, we have found that phosphorus impurity doping of SiC can be carried out below 1400°C by solid state diffusion when assisted by a process to intentionally create vacancies [1,2,3]. Such process includes oxidation or silicidation [1,3]. The silicidation version of this vacancy-assisted impurity doping (VAID) technique can be performed by depositing a layer consisting of nickel and phosphorus oxide on top of SiC.…”
Section: Introductionmentioning
confidence: 99%
“…This diffusion in 4H-SiC is performed at different temperatures ranging between 1150 and 1300 ∘ C during 30 min by our new method patented in USA and Uzbekistan and described in detail [17][18][19][20][21][22][23][24][25][26]. Below some information about new method of diffusion is given briefly.…”
Section: Methodsmentioning
confidence: 99%
“…This technique requires an assisting mechanism that can create silicon or carbon vacancies, which then facilitate impurity incorporation in the lattice. Compelling data and thermodynamic arguments (Mendis et al, 2010;Tin et al, 2010) show that the general approach of vacancy creation to assist subsequent impurity doping is feasible. Oxidation and silicidation are the two methods that have been studied for phosphorus and boron doping of 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%